Clinical efficacy and safety of fluoroquinolone containing regimens in patients with Mycobacterium avium complex pulmonary disease. Issue 4 (23rd April 2020) - Khadawardi, Hadeel; Marras, Theodore K.; Mehrabi, Mahtab; Brode, Sarah K.
Mycobacterium avium complex pulmonary disease (MAC-PD) is an increasing problem worldwide [1]. The American Thoracic Society/Infectious Diseases Society of America (ATS/IDSA) guidelines recommend a macrolide-ethambutol-rifamycin combination as first-line treatment for MAC-PD (standard triple therapy) [2]. This therapy results in microbiological success in only 52–60% of patients [3, 4]. Treatment discontinuation or modification due to toxicity is common [5, 6]. Fluoroquinolones are frequently prescribed for MAC-PD [7]. Although favourable activity has been shown in vitro and in mouse models [8], there is little clinical evidence supporting their efficacy and safety for MAC-PD [9–11]. We sought to investigate treatment outcomes and adverse events among MAC-PD patients treated with fluoroquinolone-containing therapy versus standard triple therapy. Fluoroquinolone containing regimens for Mycobacterium avium complex pulmonary disease demonstrated similar treatment outcomes, but more adverse events, than standard triple therapy http://bit.ly/2RdlFpa